Analysis of Implementation of the Merdeka Curriculum in Science Learning at SMP Negeri 4 Hulu Sungai Tengah - Saidatun Nikmah; Maya Istyadji; Mella Mutika Sari; Fahmi (Jurnal Penelitian Pendidikan IPA, 2023)
Research has been conducted on science learning using the Merdeka Curriculum. This study aims to analyze the implementation, student responses, supporting factors and inhibiting factors of the Merdeka Curriculum in science learning at SMP Negeri 4 Hulu Sunga Tengah. The type of research used in this study is a qualitative research with descriptive qualitative methods. The instruments used in this study were interview guides, observation sheets and documentation records. The research results show that the implementation of the Merdeka Curriculum in science learning at SMP Negeri 4 Hulu Sungai Tengah is still in the adaptation stage by teachers and students. Student responses were positive towards science learning with the Merdeka Curriculum. Supporting factors for implementing the Merdeka Curriculum are teachers who are competent in using technology, teacher self-motivation, independence in training and learning communities, more contextual learning concepts, and the application of PMM. Meanwhile, the inhibiting factors are that teachers still lack understanding in implementing the Merdeka Curriculum, especially P5, busy teaching schedules, additional teacher duties, and conceptual errors in implementing the Merdeka Curriculum.